Precisions on liabilities, accruals and contingent liabilities based on the theory of probabilities - Castañeda Moreano, Rosa Milagros (2021)
Objective: To describe the concepts of liabilities, accruals and contingent liabilities based on relevant aspects of the Theory of Probabilities. Method: The research was qualitative, descriptive, and non-experimental, with the use of the deductive-inductive method, based on the International Financial Reporting Standards (IFRS) content analysis and Probabilities Theory. Results: The results show discrepancies in the concepts of passives, provisions and contingent liabilities, including those raised by IAS 37 and the Conceptual Framework for Financial Reporting, also considering relevant aspects of the Theory of Probabilities. Conclusion: There are conceptual divergences between IAS 37 and the Conceptual Financial Reporting Framework in regards to the definition of liabilities, provisions or contingent liabilities, which could have a significant impact on the financial statements, as well as their poor interpretation.